Speak of Me As I Am : the Life and Work of Masud Khan. - Cooper, Judy (Karnac Books, 1993)
Judy Cooper has unravelled the many enigmas and perplexities of Masud Khan's intriguing personality ... a work of exquisite scholarship based on careful scrutiny of unpublished documents and extensive interviews with those who knew Khan intimately.